Perancangan Sistem Informasi Perpustakaan Berbasis Web Pada UPT SMP Negeri 34 Gresik - Muhammad Al Amin; Farhanna Mar’i (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Technical advances in computer applications have led to the creation of these library information systems, which are anticipated to support and facilitate the human workforce. It is anticipated that this technology will help with daily tasks in an effective and efficient manner as well. The subject of this study is the library system. There are obstacles in UPT Library SMP 34 GRESIK, and one of them is that the library still uses its service manual procedures, indicating the need innovation and change in the form of a cohesive system to accompany and prepare children in the classroom The library service information system provided by this network-based library information system should make it easier for students to find information and check out books, as well as for librarians to manage information about books and student loans. The waterfall approach was used by the author. To create this internet-based library resource system. The process of implementing this library information system begins with soft requirement analysis, prioritizing the process of borrowing books. Waterfall design techniques are used throughout the design stage, which involves creating a database with MySQL and building a user interface. Relationships are built in the database architecture using Entity Relationship Diagrams and Logic Relationship database (Database) structures.